MO350ACUTE KIDNEY INJURY RELATED TO ENDOSCOPIC RETROGRADE COLANGIO-PANCREATOGRAPHY IS ASSOCIATED WITH INCREASED INCIDENCE OF IN-HOSPITAL MORTALITY. (29th May 2021) - Gadalean, Florica; Florina, Parv; Schiller, Adalbert; Bob, Flaviu; Gluhovschi, Cristina; Oana, Milas; Mihaescu, Adelina; Simulescu, Anca; Golea-Secara, Alina; Chisavu, Lazar; Grosu, Iulia Dana; Marc, Luciana; et al.
Abstract: Background and Aims: To date, endoscopic retrograde colangio-pancreatography (ERCP) represents a major advance in gastro-intestinal endoscopy. The ERCP is a safe and minimally invasive therapy for pancreatic-biliary diseases. Adverse events (AEs) associated to ERCP are well described. However, little is known about acute kidney injury (AKI) associated to ERCP. The aim of this study was to evaluate the incidence of post-ERCP AKI and the risk factors for AKI development. The prognostic implication of ERCP-associated AKI in in-hospital mortality has been also assessed. Method: In this prospective observational study, we evaluated 396 patients who underwent ERCP, from the 3rd January 2019 through the 27th January 2020. AKI was defined as an increase in serum creatinine (SCr) ≥ 0.3 mg/dl or an increase in SCr ≥ 50% and/or by a decrease in urine output to 0.5 ml/kg/hour for 6 hours, in the first 48 hours following ERCP. Logistic uni- and multivariable regression methods were used to determine predictors of AKI and in-hospital mortality. A two-tailed value <0.05 was considered significant. Results: In the studied group, median age was 69 years, interquartile range [IQ =17], 183 (46.21%) patients being males. ERCP-associated AKI was detected in 103 patients (26%). Univariable regression analysis showed that AKI was associated with baseline eGFR (r=0.246, P<0.001), age (r=0.108, P=0.04), Charlson Comorbidity Index (CCI) (r=0.239, P<0.001), and with the following pre-ERCP parameters: systemic inflammatory response syndrome (SIRS) (r=0.125, P=0.012), serum albumin (r= -0.232, P<0.001), C-reactive protein (r=0.246, P<0.001), hematocrit (r= -0.130, P=0.009), platelet count (r=-0.155, P=0.001), total bilirubin level (r=0.230; P<0.001), alaninamino transferase level (r= -0.101, P=0.044), and alcaline phosphatase level (r=0.286, P<0.001). In the multivariable regression analysis, the independent predictors of AKI were: baseline eGFR (adjusted odds ratio (OR) 0.941, 95% confidence interval (CI): 0.927–0.956, P<0.001), CCI score (OR=1.17, 95%CI: 1.05-1.32, P=0.005), SIRS (OR=2.02, 95%CI: 1.009-4.036, P=0.047), total bilirubin (OR=1.08, 95%CI: 1.036-1.123, P<0.001), and alcaline phosphatase (OR=1.002, 95%CI:1.001-1.002, P<0.001). AKI was associated with increased in-hospital mortality (7.76 % versus 0.34 %, P<0.001). In our group, AKI was an independent predictor of in-hospital mortality (OR=9.98, 95% CI: 1.19-83.26, P=0.03). Conclusion: In patients undergoing ERCP, AKI was a common complication and an independent risk factor for in-hospital mortality. These findings highlight the importance of early AKI and AKI-related risk factors recognition, in order to minimise the risk for ERCP-associated AKI and to improve the post-ERCP outcome of patients.